Morphological and molecular characterization reveals a new species, Terriera longiparaphysium - Li, Xin-Yuan; Zhang, Peng; Zhang, Rie-Jie; Wang, Shi-Juan (Phytotaxa, 2025)
During an ongoing investigation of species in the family Rhytismataceae in Mt Huangshan, Anhui Province, China, we discovered a morphologically distinct species of Terriera on fallen leaves of Loropetalum chinense (Hamamelidaceae). Multigene phylogenetic analyses (ITS, nrLSU, mtSSU) combined with morphological characteristics of the ascomata, asci and paraphyses, confirmed the distinctiveness of this species. It is described here as a new species, Terriera longiparaphysium.